Grand Theories and Ideologies in the Social Sciences
XI, 266 p.
Keywords: This book analyzes the main competing grand theories in the social sciences, including developmentalism, dependency analysis, Marxism, institutionalism, rational choice, Freudianism, environmentalism, sociobiology, neurosciences, and transitions to democracy.